Application of the Prototype Method in the Export Section Goods Delivery Document Monitoring System - Sari, Meri Mayang; Iskandar, Dedy; Supriadi, Ajay; Sudarto, Ferry; Saptono, Arief (Journal Sensi: Strategic of Education in Information System, 2024)
Companies can now handle and organize data systematically thanks to advances in information technology. Monitoring is a daily assessment (evaluation) of activities and progress. On the other hand, evaluation is an assessment carried out periodically regarding all achievements. Well-managed data will help companies make decisions. PT Gajah Tunggal Tbk is engaged in the manufacturing industry which meets customer needs by making product samples. One of the problems is that document control is carried out manually, which makes obtaining product trial data difficult. Additionally, there is no storage space for product sampling documents, which results in loss or damage to copies of documents. Product sampling is used according to customer needs, allowing companies to develop new products that meet customer or customer needs. Thus, the products produced will try to meet customer satisfaction. The aim of this research is to improve the services provided by PT Gajah Tunggal Tbk by building a goods delivery document monitoring system using the prototype method. To achieve this goal, previously built systems must be evaluated. The results obtained from monitoring goods delivery documents can increase the efficiency and efficiency of the service process with shorter waiting times and simpler delivery procedures. Using the prototype method can help PT Gajah Tunggal Tbk improve the efficiency and performance of its services.